Analysis of hemodialysis and graft representations in patients with chronic renal failure: an anthropological approach - Desseix, Aurélie; Merville, Pierre; Couzi, Lionel (Néphrologie & thérapeutique, 2010)
Hemodialysis and kidney transplant are two treatments for renal failure, which lead to numerous changes in the patients' way of life. We have questioned ourselves on the different ways they could deal with those changes by studying the representations and the ritualisation that surrounds the sick. From 2005 to 2007, qualitative interviews, based on the method of life stories, were conducted with 35 patients with chronic renal failure in three Aquitaine's centres. The results show three main groups of representation both in pre-transplant and in post-transplant. Specific behaviours are tied to each group of representation that are beneficial or deleterious with respect to treatment or the patient's social life. We will show that, on the one hand, the patients who see the hemodialysis treatment as a traditional rite of passage cope with the situation more easily and on the other hand, we will stress that this representation is closely linked to how the patients will later accept the kidney transplant. So, we have been able to link the representations of hemodialysis patients and transplant experience. Then these results have a practical consequence for the caregivers who can use the tools of anthropology (the interview guide, analysis grid) through a program of therapeutic education, to precociously take care of patients who are likely to come up against issues after their kidney transplant.